Plasmonic Nanoparticle Integration on Fiber Optic: Role of Organic Linker and Functionalization Length in Refractive Index Sensing - Ilmiyah, Shela; Syahadi, Mohamad; Muflikhah, Muflikhah; Pradana, Yuwana; Supardi, Zainul Arifin Iman; Darmadi, Iwan; Aprilia, Lia (Makara Journal of Science, 2025)
Nanoplasmonic fiber optic sensors leverage the optical fiber’s inherent compactness and surface sensitivity via evanescent-field interactions with the localized surface plasmon resonance of the metallic nanoparticles. One of the popular approaches is self-assembly owing to its relatively low cost. Despite its low cost, the self-assembly technique has low reproducibility and exhibits low sensitivity because of low nanoplasmonic coverage on the fiber optic surface. In this study, several fabrication techniques were explored to assess the refractive index sensitivity by comparing three common organosilanes, i.e., (3-Aminopropyl)triethoxysilane (APTES), (3-Aminopropyl)trimethoxysilane, and (3-Mercaptopropyl)trimethoxysilane. Comparative analyses assessed the anchoring efficiency of the three silanes, sensor reproducibility, functionalization-length sensitivity, and the sensor’s ability in glucose detection (5%–50%) in the reflection and transmission modes. As a result, the APTES-promoted sensor exhibited the best sensing sensitivity among the others, likely owing to their more uniform monolayer formation and the more favorable interaction between NH₂ groups and Au nanoparticles compared with SH groups. Glucose sensing displays a sensitivity of 0.196 nm/%glucose (for reflection) and 0.389 nm/%glucose (for transmission). The limits of detection were 19.44% (for reflection) and 5.71% (for transmission). This study provides important perspectives for the potential use of nanoplasmonic fiber optic sensors in biological and chemical sensing.